Increasing the accuracy of the non-contact temperature measurement in the case of energy audits of different objects - Cherepashchuk, Grygorii; Kalashnikov, Evgeniy; Nazarov, Alexander; Siroklyn, Vitalii (Technology audit and production reserves, 2017)
The object of research is the process of thermal inspection of enclosing structures with the help of a thermal imager. One of the most problematic places of thermal imaging energy is the presence of a significant methodological error. The reason for this is a large number of factors affecting the process of measuring the temperature of the surfaces of objects in thermal imaging diagnostics. In the course of the study, methods were used to analyze and isolate the factors that have the greatest effect on the thermogram of the investigated object. Results are obtained on the evaluation of the influence degree of each influencing factor on the measurement result and the total methodical error from simultaneous influence of all influencing factors is estimated. The total methodical error of thermal imaging energy surveys (up to 4 %) is estimated. This is due to the fact that the proposed methods for improving the accuracy of energy audit have a number of features, in particular, the result of energy audit largely depends on the experience and qualification of the operator. But the use of the proposed recommendations allows the operator to make measurements at a high professional level. Thanks to this, it is possible to improve the accuracy of the energy audit. In comparison with similar known energy audit methods, the proposed method makes it possible: to reduce the methodical error of thermal imaging energy surveys, to increase the energy efficiency of buildings and to reduce the cost of their heating.